1991
DOI: 10.1016/s0006-3495(91)82158-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen ion currents in rat alveolar epithelial cells

Abstract: Alveolar epithelial cells isolated from rats and maintained in primary culture were studied using the whole-cell configuration of the "patch-clamp" technique. After other ionic conductances were eliminated by replacing permeant ions with N-methyl-D-glucamine methanesulfonate, large voltage-activated hydrogen-selective currents were observed. Like H+ currents in snail neurons and axolotl oocytes, those in alveolar epithelium are activated by depolarization, deactivate upon repolarization, and are inhibited by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
156
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 57 publications
12
156
0
3
Order By: Relevance
“…The first electrophysiological recording of voltage-dependent proton current in snail neurons were reported by Thomas and Meech [120]. Later studies, primarily done by DeCoursey group [121][122][123], found similar currents in other cell types [124]. However, controversy in the field on whether proton channels were in fact molecular entities had been present since 1989 after studies from Byerly and Suen [125].…”
Section: Discovery Of the Voltage-gated Proton Channel Hv1mentioning
confidence: 99%
“…The first electrophysiological recording of voltage-dependent proton current in snail neurons were reported by Thomas and Meech [120]. Later studies, primarily done by DeCoursey group [121][122][123], found similar currents in other cell types [124]. However, controversy in the field on whether proton channels were in fact molecular entities had been present since 1989 after studies from Byerly and Suen [125].…”
Section: Discovery Of the Voltage-gated Proton Channel Hv1mentioning
confidence: 99%
“…Rat alveolar epithelial cells express a high density of voltage-gated proton channels (18,24,25), with properties different from those in neutrophils. No consistent change in either the H ϩ current amplitude or in gating kinetics was detected in six epithelial cells studied for up to 45 min after PMA treatment (data not shown).…”
Section: As Illustrated Inmentioning
confidence: 99%
“…However, the flux of K ϩ ions, carried by valinomycin, can balance the charge generated by H ϩ movement, enabling extended observation of both inward and outward fluxes of H ϩ ions, driven by ⌬p. Electrophysiological studies have demonstrated the presence of voltage-activated H ϩ conductance in snail neurons (30), muscle cells (31), oocytes (32), epithelial cells (33), and phagocytes and phagocyte cell lines (34 -36). The currents are elicited from cells exposed to a large pH gradient (Ն1 pH unit) by the imposition of positive membrane potentials (Ն ϩ40 mV).…”
Section: Histidines In Gp91mentioning
confidence: 99%